“Uma questão mesmo de sobrevivência”: Professores de Ananindeua (PA) e a Educação Ambiental nas aulas de História - CORDOVIL, Wendell Presley Machado (2021)
This work presents the analysis of interviews with a semi structured questionnaire carried out with History teachers in the city of Ananindeua (PA Brazil). Here, it seeks to understand the perception of these 14 teachers about the relationship between Environmental Education (EE) and History Teaching. For that, it is concerned with analyzing the representations of the interview ed teachers about important concepts for EE: Nature, Environment and the very concept of Environmental Education. Furthermore, it is intended to observe how these teachers perceive the relationship of environmental issues with historic al processes and hist ory classes . The results point to plural representations of the concepts of Environmental Education and Nature, in many moments being comparable to the categories of conceptions presented in bibliographies, but in others being nec essary to build new catego ries. Even with most teachers pointing out the importance of Nature for the historical processes and of Environmental Education for the Teaching of History, they point out difficulties for the insertion of the environmental discussion in their History clas ses.